Strategies to promote self-esteem, autonomy and self-care practices for people with chronic wounds - Liarine Fernandes Bedin; Josefine Busanello; Graciela Dutra Sehnem; Fernanda Machado da Silva; Márcia Adriana Poll
This is a qualitative study of an exploratory nature that aims to identify the strategies used by nurses in primary care, in situations involving nursing care, to promote self-esteem, autonomy and self-care practices for people with chronic wounds. The study included eight nurses. Data were collected by means of a focus group in July 2012. The thematic analysis technique was used to identify the following categories: Nursing care from the perspective of comprehensiveness; Recovering support networks: family and social movements; Multidisciplinary work; Autonomy and nurses. It was concluded that the presented strategies value, above all, the social environment of these individuals, the family, religion and the nurse's approximation to the realities of people with chronic wounds.